STRATEGI PEMBELAJARAN DARING MELALUI ZOOM MEETING - Nina Wibowo; Meidawati Suswandari; Efa Widyastuti (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
This study aims to describe online learning strategies through Zoom Meeting s for sixth grade students at Sugihan 03 State Elementary School Sukoharjo. This type of research uses a qualitative approach. The subject of this research is the sixth grade teacher at Sugihan 03 State Elementary School Sukoharjo. The data collection tool used is interviews. The data analysis techniques of this research are data reduction, data presentation and conclusion drawing. The results of this study indicate that online learning through Zoom Meeting s greatly influences digital literacy skills for teachers and children. The method in online learning that is often used uses Project Based Learning.